Dampak penggunaan media sosial intensif terhadap kesehatan mental generasi muda - Mustofa, Muhammad Royhan (Maliki Interdisciplinary Journal, 2025)
In this study, researchers investigated the consequences of excessive social media use on young people’s mental health. The proliferation of social media in widespread use by adolescents and young adults is a phenomenon of the last decade. Along with its usefulness in connecting individuals as an information and communication technology there are also concerns about the impact on the mental health of its users. This research notes that young people in particular potentially face an increased risk of depression, anxiety and sleep disorders as a result of their frequent use of social media. Through constant exposure to the pressure to present a perfect life and gain social validation through likes and comments, the younger generation is vulnerable to decreased self-esteem and increased feelings of loneliness. The study also discusses a range of measures to reduce the negative impact of social media use, educational approaches that increase digital literacy and mental health awareness, as well as with policy regulations that focus on reducing commercial exploitation and unhealthy social pressures within social media platforms. In conclusion, this study emphasizes the importance of a holistic and sustainable approach to managing social network use among adolescents so that they can reap the benefits without compromising their mental health.